The Implications of COVID-19 Pandemic on Dollar Exchange Rate of Pakistan - Akhtar, Ayaz; Abiad, Mohammad; Mashwani, Wali Khan; Aamir, Muhammad; Naeem, Muhammad; Khan, Dost Muhammad (Frontiers in Applied Mathematics and Statistics, 2022)
The Coronavirus disease (COVID-19) most likely began in an animal species and was subsequently transmitted to humans in Wuhan, China, a city of 11 million people, on December 29, 2019, when the first case was recorded. The Coronavirus is then transmitted from person to person by infected droplets from a sick person's coughing, sneezing, or contaminated hands. Hence, the purpose of the study is to see the impact of the outbreak of COVID-19 daily tests on the Pakistani rupee against the US dollar exchange rate using the Vector Autoregressive approach. The data is gathered from February 26, 2020, to March 2021. This period was selected because the pandemic expanded, and the first case was observed in Pakistan on Feb 26th 2020. To verify this effect, A Vector Autoregressive Model was developed. A generalized version of the Autoregressive Model is a Vector Autoregressive (VAR) model. As a result of the COVID-19 pandemic, the Pakistani rupee devalued against the US dollar throughout the abovementioned period. When analyzing the Pakistani rupee versus the US dollar exchange rate using a Vector Autoregressive Model, the values of the lags (1, 4, 6, and 7) of the explanatory variable have a significant impact. Besides, under the VAR model, the IRF (Impulse Response Function) asserted the actual impact of the daily COVID-19 tests, as well as Decomposition of Variance, was shown to provide for the daily COVID-19 tests just a small part in understanding the volatility of the Pakistani rupee against the US dollar exchange rate. The Granger Causality suggests that the short-term and long-term changes in the Pakistani rupee against the US dollar exchange rate are caused by daily COVID-19 tests.